Development of vision-based sensor of smart gripper for industrial applications - Hasimah, Ali; Tei, Chen Seng; Low, Hoi Hoi; Mohamed Elshaikh (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/